2017
DOI: 10.1159/000468946
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIII Deficiency and Thrombocytopenia Are Frequent Modulators of Postoperative Clot Firmness in a Surgical Intensive Care Unit

Abstract: Objective: Fibrinogen and factor XIII (FXIII) have been shown to critically influence clot firmness in the intraoperative setting and thus likely influence intraoperative bleeding. We were interested to identify potential modulators of postoperative clot firmness in a tertiary care hospital surgical intensive care unit setting, independent of their clinical course during surgery. Methods: 272 day-shift consecutive patients were evaluated for whole blood clot firmness evaluated by the ROTEM® EXTEM thrombelastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 73 publications
(75 reference statements)
4
20
0
Order By: Relevance
“…Table 1 also includes the frequencies for the respective deficiencies if lower cut-off levels than regular reference range borders were used. Not unexpectedly, these results closely match ones in the early postoperative setting [ 16 ].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Table 1 also includes the frequencies for the respective deficiencies if lower cut-off levels than regular reference range borders were used. Not unexpectedly, these results closely match ones in the early postoperative setting [ 16 ].…”
Section: Resultssupporting
confidence: 84%
“…A very rare entity of acquired FXIII deficiency is a hemophilia-like disease caused by an anti-FXIII antibody, leading to potentially life threatening bleeding events [ 15 ]. By far the most prevalent reason for acquired FXIII deficiency is consumption in the surgical setting [ 16 ]. Treatment therefore mostly consists of FXIII substitution, sometimes in combination with immunosuppressive therapy if an autoimmune or specific inhibitory component is present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only scarce knowledge on the relationship between thromboelastometry or thromboelastography and conventional parameters of hemostasis exists [2]. Thus, it is important to research such relationships; new research presented here shows that factor XIII, alone and in combination with other parameters, has a frequent and profound effect on postoperative clot firmness [3].…”
mentioning
confidence: 82%
“…Various preclinical models of stroke have shown that rapid hematoma clearance after hemorrhagic stroke ameliorated inflammation and improved neurological deficits in the short and long terms [28]. Rappard et al [29] found that the blood clot firmness is highly depending on the platelet count and that thrombocytopenia results in a soft unstable clot. Similarly, thrombocytopenia may help in the decrease of clot formation with its sequelae of blockage, barrier impairment, and inflammatory reaction, and even if the intraventricular hematoma is formed it is not firm and usually resorbs faster.…”
Section: Correlation Between Thrombocytopenia and The Development Of Phhmentioning
confidence: 99%